School Health Education and Teachers' Preservice Training: The Case of Greece - Pelagia Soultatou; Kyriacos Athanasiou (MDPI AG, 2024)
Background: School health education (SHE) serves as a primary pedagogical aspect of public health. This study aims to explore the curricula of preservice schoolteachers, examining whether graduate courses in Greek universities include SHE, how it is structured, and whether critical pedagogy principles are integrated. Methods: A corpus of n = 21 documents was compiled, encompassing all educational departments in Greek higher education, including Departments of Early Childhood Education and Care (n = 3), Departments of Preschool Education (n = 9), and Departments of Primary Education (n = 9). Results: Content analysis revealed the presence of SHE in 11 out of 21 educational departments. Thematic analysis uncovered significant variability in the curricula, with greater emphasis placed on health-related topics rather than the methodologies and values of SHE. Critical pedagogy principles were not explicitly evident in the curricula, while a persistent biomedical orientation left little room for the development of concepts related to social justice. Conclusions: This study represents the first of its kind in Greece and among the few internationally to examine preservice training for schoolteachers in SHE. The findings underscore the need for revisions to align with the key lessons learned from the major public health crisis of the COVID-19 pandemic. It is imperative to acknowledge that vulnerabilities have been exacerbated, and inequalities widened, necessitating a reassessment of current approaches to health education within teacher training programs.